Assessing the Efficiency of Effluent Treatment Plant in comparison with Traditional Sand Filtration System (OODBODHAN, 2026)
This study evaluates the Effluent Treatment Plant (ETP) based on its infrastructure, operational efficiency, maintenance practices, and overall performance in treating wastewater generated from hospital premises. A comparative analysis of water quality parameters before and after treatment was carried out for both the initial phase and the present condition of the ETP. For efficiency assessment, samples were collected from seven designated points over five different days at varying time intervals. These sampling points included the inlet/raw influent at the equalization tank, the SAFF reactor, the outlet from the mechanical tank, and the outlet of the traditional sand filtration unit, covering points 1 to 7. The pH values at the inlet were found to be acidic to neutral, whereas the outlet pH was alkaline. The average removal efficiencies for TDS, TSS, turbidity, COD, and BOD were found to be 34.39%, 69.78%, 23.27%, 64.59%, and 79.23%, respectively. The mechanical treatment system showed an efficiency of 60.83%, while the traditional sand filtration system demonstrated an efficiency of 57.96%.A comparison with historical data from 2053 BS revealed that the efficiencies for TSS, turbidity, COD, and BOD were 80%, 25.45%, 75.27%, and 95.94%, respectively, whereas in the present year these values have declined to 77.82%, 23.02%, 74.11%, and 91.02%. Accordingly, the reduction in performance of the treatment plant from 2053 to 2081 was observed to be 2.66% for TSS, 9.34% for turbidity, 4.08% for COD, and 2.06% for BOD. The findings indicate that the ETP is more effective than the traditional sand filtration system. However, the overall efficiency recorded in 2053 was significantly better than in the present year, suggesting that the ETP now requires improved maintenance and preservation to restore its performance.